(The poetry of instinct (a poem of Ta‘abata Sharan "O Eid Malik" as a model - Al Ruwaili, Hamda Mourif Eid Makhlaf (Journal of Humanities & Social Sciences, 2017)
Literature is the tool through which we extract what is in nature from perfection،  especially that man is prepared to accept this perfection،  prepared for him instinctively،  and hence came this research "the poetry of instinct."In which the researcher tried to expose the concept of instinct،  through the definition of language first،  and then clarify the concept in literature،  and the opinion of the writers in it.   The researcher pointed out that the meaning of "print"،  which expresses the aunt of the writer affects the souls of others،  especially if this poetry embodies a set of values ​​and virtues of the Arabs،  which is closer to the typical self of the Muslim man as portrayed by MuslimsIt turns out that this finalism is a general view that dominates the hair of the thorns starting from the lexicon،  and ending with meaning and vision. This text،  "Ya'id Malik، " confirms that the general meaning of the text،  which is the coarse nature of the poet،  can only be liberated through the holistic and universal vision of the text. The meaning is formed only through this holistic view. The effect of the last word is at least the first word effect in the text.Finally،  it is clear that the general significance of the poem is to mourn the dignity of the soul and its institutions،  and the revolution against the customs of the unjust tribe،  which is humiliated and humiliated by establishing new rules for a society of justice،  interdependence،  brotherhood and equality in accordance with authentic Arab values. Roughness ".
Keywords: innate; moral values; poetic experience; social reality; roughness; revolution